Dr. Wortle's School - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2007)
"Dr. Wortle's School" by Anthony Trollope is a novel published in 1881. Set in Victorian England, the story centers on a respected Christian academy thrown into scandal when it's discovered that two hired teachers, Mr. and Mrs. Peacocke, are living in an invalid marriage. Her first husband, believed dead, has reappeared alive. Dr. Wortle must defend his decision to support the couple while his school's reputation crumbles and the community condemns their unconventional relationship as sinful. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Doctor_Wortle%27s_School
Release date is 2007-06-18
E-text prepared by Stanford Carmack
Keywords: England -- Fiction; Domestic fiction; Married people -- Fiction; Extortion -- Fiction; Classicists -- Fiction; School principals -- Fiction; Americans -- England -- Fiction